Peningkatan Pelayanan Tamu melalui Pelatihan Pembuatan Welcome Drink Mocktail bagi Pengelola Homestay di Desa Kemiren - Martalia, Diana; Handoko, Rudi Tri; Yuniarti, Claudia Oktavia Putri (Abdibaraya, 2026)
This community service activity aims to provide training on making mocktail-based welcome drinks using local ingredients for homestay managers in Kemiren Village, Banyuwangi. This training is conducted to address the challenge of improving service quality, particularly in welcoming guests, in order to maintain destination loyalty and competitiveness. Innovative welcome drinks are considered important because they have the potential to create a unique selling proposition (USP) and enhance the experiential value for guests, but they have not been utilized due to a competency gap among managers. The method applied is participatory training based on experiential learning, which integrates theoretical material, demonstrations, and hands-on practice involving six manager representatives. As a result, participants successfully mastered mixology techniques such as stirring, layering, shaking, and muddling, and were able to mix drinks such as Lemon Coffee Tonic using local ingredients. This training successfully addressed skill gaps, built the confidence of managers, and empowered the potential of local ingredients to create a USP. The impact of the activity is expected to improve service quality, guest experience value, and support the sustainability of the village's economy and tourism through service differentiation that is in line with the local identity